An analysis of malignant tumour incidence in the male population of Poland in the period 2006–2010 - Domżał-Drzewicka, Renata; Gałęziowska, Edyta (Contemporary Oncology/Współczesna Onkologia, 2015)
In the period 2006–2010, the National Cancer Registry indicated a gradual increase in the incidence of malignant tumours among men, from 64,092 thousand in 2006 to 70,024 thousand in 2010. In the reference period, the number of deaths due to malignant tumours among men oscillated around 52 thousand. The aim of this study was to analyse the incidence of malignant tumours in the male population of Poland in the period 2006–2010. The study material comprised data obtained from the National Cancer Registry and from the Central Statistical Office, available on the websites of these institutions. The malignant-tumour incidence rate among the male population in 2006–2010 showed a slow but steady growth, while the death rate dropped slightly at the end of 2010. The hypothesis that the cancer-incidence risk grows with age has been proven, and a substantial increase in this risk is observed from the fourth decade of life. The most common malignant tumours in Poland in the analysed period included lung cancer, followed by prostate cancer and colorectal cancer. Future prophylactic and educational programmes should be addressed to men prior to reaching the age of increased cancer risk.